Systematic Literature Review: Kemampuan Koneksi Matematis pada Model Problem Based Learning Rentang Tahun 2019-2023 - Wardani, Christina Anindya Kusuma (Indonesian Journal Publisher, 2024)
The abilities that students need to master when learning mathematics include mathematical connection skills. The improvement of mathematical connection skills can be achieved through a learning model that requires students to participate in the problem-solving process, such as the Problem-Based Learning (PBL) model. This research aims to analyze the results of PBL model research on mathematical connection skills and identify research trends related to mathematical connection skills in the PBL model from 2019 to 2023. The chosen method is Systematic Literature Review (SLR) on all articles indexed in Google Scholar. Based on the research articles, mathematical connection skills can be enhanced through the PBL model. Furthermore, research related to mathematical connection skills in the PBL model was most frequently published in 2019 and conducted predominantly at the Junior High School (SMP) level.